Online Marketing Dan Labelisasi Produk Sebagai Terobosan Pemasaran Pada UMKM Tas Anyaman Di Desa Nailan Ponorogo - Febrilyantri, Candra; Cahya Firman Syah (Amaluna: Jurnal Pengabdian Masyarakat, 2022)
Woven bag crafts is one of the Micro, Small, and Medium Enterprises (MSMEs) located in Nailan Village, Slahung District, Ponorogo Regency, and has been running for almost three years since 2019. Woven bag products are increasingly popular among the community. However, there are obstacles when doing marketing, namely not being able to reach outside the Ponorogo district; besides, this product still needs to have a label that can influence people's buying interest. Therefore, assistance is necessary for making labels and marketplace accounts so that product sales can be carried out widely. These activities for business owners take advantage of opportunities, potential, and technology to maximize business profits. The method used is ABCD, namely finding assets owned by the community and optimizing them. The results obtained from the mentoring activities have succeeded in helping woven bag business owners in Nailan village, Slahung sub-district, and Ponorogo district makes product labels and uses technology to increase sales.